Correction: Exercise prescription for the prevention and treatment of chronic diseases in primary care: Protocol of the RedExAP study. - Alicia Saz-Lara; José Alberto Martínez Hortelano; María Medrano; Raquel Luengo-González; Miriam Garrido Miguel; Montserrat García-Sastre; José Ignacio Recio-Rodriguez; Daniel Cuesta-Lozano; Iván Cavero-Redondo (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0302652.].